The Confluence of Perceiving and Thinking in Consciousness Phenomenology - Wagemann, Johannes (Frontiers in Psychology, 2018)
The processual relation of thinking and perceiving shall be examined from a historical perspective as well as on the basis of methodically conducted first-person observation. Historically, these two psychological aspects of human knowledge and corresponding philosophical positions have predominant alternating phases. At certain historical points, thinking and perceiving tend to converge, while in the interim phases they seem to diverge with an emphasis on one of them. While at the birth of modern science, for instance, these two forms of mental life were deeply interlinked, today they seem to be separated more than ever before – as a number of scientific crises have shown. Turning from the outer to the inner aspect of this issue, a phenomenological view becomes relevant. In terms of the consciousness phenomenology developed by Steiner (1861–1925) and Witzenmann’s (1905–1988) Structure Phenomenology, this article will show how a methodical integration of thinking and perceiving can be carried out on the basis of first-person observation. In the course of a skilled introspective or meditative self-observation the individual’s own mental micro-actions of separating and integrating come into view, jointly constituting what we usually call thinking and perceiving. Consequently, this approach includes a conceptual as well as a perceptual dimension the experimental confluence of which ties in with the methodological core principle of modern natural science. At the same time, making this principle explicit may open the way to a further development of human consciousness and its scientific delineation.